Insights into Collaborative Research on Emerging Media Impact on Consumer Behavior: Wawasan tentang Penelitian Kolaboratif tentang Dampak Media yang Sedang Berkembang terhadap Perilaku Konsumen - Amalia , Fara Putri; Puspitasari, Puspitasari; Saputra , Muhammad Rizky; Abadi , Totok Wahyu (House of Wisdom: Journal on Library and Information Sciences, 2024)
This study conducts a bibliometric analysis from 2010 to 2023 using Crossref data to explore trends in research on mass media and social media's impact on consumer behavior. Analysis using VOSviewer software reveals "media" as the dominant keyword, with emerging interests in topics like misinformation and pandemic-related influences. Collaborative authorship highlights Barnard, Stephen R, and Linder, Andrew M, each contributing significantly. This research underscores current themes and identifies gaps for future studies, emphasizing the evolving dynamics of media's role in shaping public consumption behaviors. Highlights: Mapping Trends: Bibliometric analysis of mass and social media's impact trends. Emerging Topics: Misinformation, pandemic influences in consumer behavior literature. Authorship Impact: Barnard, Stephen R, and Linder, Andrew M's collaborative contributions highlighted. Keywords: Bibliometric analysis, mass media, social media, consumer behavior, collaborative authorship